Die Niederschlagungsverhältnisse im Uva-Becken auf Ceylon.: Eine geländeklimatologische Untersuchung - Domrös, Manfred (ERDKUNDE, 1969)
The influence of relief on the spatial distribution and quantity of precipitation was studied using the example of the Uva Basin in Ceylon. It is part of the eastern slope of the Ceylonese Highland and is almost surrounded by mountain ridges and massifs of various elevations (Fig. 1). For this purpose unpublished long-period annual and monthly precipitation means for 109 recording points, pre dominantly in tea plantations, were evaluated and, with their help, the analysis of phenomena of terrain climatology was attempted: 1. During the south west monsoon over Ceylon, there was a statistically certain windward and lee effect through the Central Highland, on which the dry period in the Uva Basin from June to September depends (Figs. 4 and 5). This phenomenon is further modified by diurnal winds; in weather terms it can be demonstrated by the Föhn wall. 2. The vertical distribution of precipitation during adiabatic rain caused by depressions and cyclones (Fig. 6) and also in adiabatic rain caused by the monsoon stream blowing from the north east was studied during the north east monsoon (December to February) using the example of the south and east rims of the Uva Basin; however, the rise in precipitation with increasing altitude which is characteristic of adiabatic rain was not observable. In both examples there was no certain relationship between amount of precipitation and altitude. In contrast, analysis of vertical precipitation distribution in the case of convectional rain (Fig. 8) showed that, in the inter-monsoon months, March, April, May, October and November, after a preliminary increase of precipitation with increasing altitude, a decrease of precipitation occurred above a critical height between 900 and 1400 metres. 3. With the aid of monthly precipitation means, the predicted influence of surface forms and plant growth on precipitation e.g. that convection was strengthened or weakened, could not be proved. The investigation of precipitation conditions in the Uva Basin of Ceylon brings nearer the point at which the general circulation and radiation conditions can be called as evidence for the spatial distribution of precipitation as well as the relief. Monthly means of weather data are not in every case adequate for the analysis of phenomena of terrain climatology; where possible pentadonal means should be used.